PENGARUH JUMLAH KUNJUNGAN KAPAL, JUMLAH PENUMPANG, DAN AKTIVITAS BONGKAR MUAT DI PELABUHAN TERHADAP PERTUMBUHAN EKONOMI DAERAH. STUDI PADA SELURUH PROVINSI DI INDONESIA - Aganaim, Ardiansyah; Mokodompit, Eliyanti Agus (Journal Economics Technology And Entrepreneur, 2025)
This study aims to analyze the impact of ship visits, passenger numbers, and cargo handling activities at ports on regional economic growth across all provinces in Indonesia. The research employs a quantitative approach with multiple regression analysis using secondary data from 36 provinces in 2023. The results indicate that cargo handling activities have a significant positive effect on economic growth (coefficients of 0.124 for unloading and 0.183 for loading), as does the number of ship visits (coefficient of 0.021). However, passenger numbers show no significant impact. These findings suggest that port operational efficiency, particularly in cargo logistics, plays a more critical role than passenger mobility in driving GDP growth. The policy implications highlight the importance of investing in port infrastructure and integrating it with local productive sectors to maximize economic benefits.